The Stela of Haremwia, Chief of the Provisioning Sector of the Temple Workshop (CG 34079 / JE 22011) - Joseph, Amgad (Études et Travaux, 2021)
This article is devoted to the description and analysis of the limestone stela of Haremwia from Abydos. It was on display in the Egyptian Museum, Cairo (CG 34079 / JE 22011) and is currently in the storerooms of the Grand Egyptian Museum, Giza. It dates to the period from the mid to the late Eighteenth Dynasty, New Kingdom, and probably from the reign of Amenhotep III, on the basis of its stylistic, iconographic, and epigraphic details. It is extremely well preserved and most of the colours are intact, apart from some damage to the bottom. The stela records a significant title of Haremwia, namely ḥry šnʿ n tȝ wʿbt, ‘chief of the provisioning sector of the temple workshop’. The importance of this stela, above all, is that it records the first attestation of this title on Egyptian monuments. Furthermore, it records Asiatic names of foreign origin for family members. The offering formula in the first register is very interesting due to the retrograde orientation of its hieroglyphic inscription. The author describes the stela, deals with its individual idiosyncrasies, inscriptions, iconographic and phraseological traits, and focuses on the titles and professions of its individuals.